The effect of interior design and visual communication on consumers' intention to use the photobooth at Kopilogi Garut - Rido Muhamad Robani; Nizar A Hamdani; Dioka Muhamad Akbar (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effects of interior design and visual communication on consumers' intention to use the photobooth service at Kopilogi Garut. A quantitative research design with an associative approach was employed using data collected from 100 consumers selected through purposive sampling. Primary data were obtained through structured questionnaires and analyzed using multiple linear regression with SPSS. The findings indicate that both interior design and visual communication have positive and significant effects on consumers' intention to use the photobooth service, both individually and jointly. The results suggest that an aesthetically appealing and comfortable interior environment, supported by informative and engaging visual communication, enhances consumer interest in utilizing experiential service facilities. This study contributes to the services marketing literature by demonstrating the complementary roles of physical environmental design and visual communication in shaping consumer behavioral intentions within hospitality and lifestyle settings. The findings also provide practical implications for café managers by emphasizing the importance of integrating attractive spatial design with effective visual communication to strengthen customer engagement and increase the utilization of value-added service facilities such as photobooths. Keywords: Interior Design; Visual Communication; Consumer Interest; Photobooth